2003
DOI: 10.1161/01.res.0000067928.83455.9c
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand (TRAIL) Sequentially Upregulates Nitric Oxide and Prostanoid Production in Primary Human Endothelial Cells

Abstract: Abstract-Endothelial cells express tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) receptors, but the function of TRAIL in endothelial cells is not completely understood. We explored the role of TRAIL in regulation of key intracellular signal pathways in endothelial cells. Key Words: tumor necrosis factor-related apoptosis-inducing ligand Ⅲ nitric oxide Ⅲ prostanoids T umor necrosis factor (TNF)-related apoptosisinducing ligand (TRAIL)/Apo-2L is a member of the TNF family of cytokines, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
105
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 38 publications
5
105
0
Order By: Relevance
“…However, others have described that soluble TRAIL, in vitro, also induces apoptosis and proinflammatory activity in normal human umbilical vein endothelial cells (HUVEC) [21]. While others have shown that TRAIL, in vitro, on HUVEC exerts anti-inflammatory activity (by increasing nitric oxide and prostanoid production) [22]. TRAIL might play an important role in modulating leukocyte/endothelial cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have described that soluble TRAIL, in vitro, also induces apoptosis and proinflammatory activity in normal human umbilical vein endothelial cells (HUVEC) [21]. While others have shown that TRAIL, in vitro, on HUVEC exerts anti-inflammatory activity (by increasing nitric oxide and prostanoid production) [22]. TRAIL might play an important role in modulating leukocyte/endothelial cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported unanticipated side effects of TRAIL, including proangiogenic-enhanced endothelial cell proliferation, migration, and cytoskeletal reorganization. 37,38 In addition, a chief concern with conventional chemotherapies is the inevitable side effects from the nonspecific biodistribution of chemotherapeutic drugs. However, to date a strategy to improve on the challenges posed by combination treatment has not been reported in the published scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore one mechanism by which MSC of bone marrow origin may contribute to atherosclerotic progression is through the release of OPG, which could act as a paracrine/autocrine growth factor for vascular SMC. OPG could also contribute to worsen the degree of atherosclerosis by inhibiting the TNF family member TRAIL (Vitovski et al, 2007), which displays anti-inflammatory activity in vitro (Zauli et al, 2003) and anti-atherosclerotic activity in vivo, as documented by studies in the apo-E null mice model (Secchiero et al, 2006b). …”
Section: Discussionmentioning
confidence: 99%